Film for use in the manufacturing process of cycloolefin polymer film and method for manufacturing the same
By forming an acid-modified ethylene-α-ene copolymer resin layer on the polyester film and controlling its composition and surface roughness, the shortcomings in the adhesion and release properties of the optical film carrier film are solved, moderate adhesion and good release properties are achieved, and production efficiency and output stability are ensured.
Patent Information
- Application Number
- JP2023051763
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-03-28
- Filing Date
- 2023-03-28
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-03-28
AI Technical Summary
In the prior art, the carrier film used to manufacture optical films has insufficient adhesion and release properties, resulting in the optical film being easily disengaged during transmission, affecting production efficiency and yield.
A resin layer composed of acid modified ethylene-α-ene copolymer and crosslinking agent is used, and the coating is carried on the polyester film. By controlling the composition and surface roughness of the resin layer, moderate adhesion and good release properties are achieved.
It is realized that the optical film is not easy to detach during the transmission process, ensuring the stability of production efficiency and output, while maintaining the surface smoothness of the optical film.
Smart Images

Figure 0007656947000001 
Figure 0007656947000002 
Figure 0007656947000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a process film that can be suitably used in the production of a cycloolefin polymer film. [Background technology]
[0002] Cycloolefin polymer (COP) is a material that has attracted attention in recent years as an optical film because it has a combination of excellent properties such as low moisture absorption, low birefringence, high transparency, high heat resistance, high moldability, low dielectric constant, and low dielectric loss tangent.
[0003] Known methods for producing COP films include extrusion molding, solution casting, etc. In the solution casting method, COP is dissolved or dispersed in a solvent, and the COP coating liquid from which insoluble matter and dissolved gas have been removed is cast or coated on a process film, which is then dried and peeled off from the process film to produce a COP film.
[0004] To obtain a high-performance COP film using the solution casting method, the process film must have three properties: excellent surface smoothness, adequate adhesion to the COP film, and excellent releasability from the COP film after drying.
[0005] As process films for producing COP films, those with excellent surface smoothness described in Patent Documents 1 and 2 are known. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2004-017435 A [Patent Document 2] JP 2014-208465 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the carrier film for optical film production in Patent Document 1 has insufficient releasability from the COP film, leaving room for improvement in product stability. The laminated film in Patent Document 2 has insufficient adhesion to the COP film, so when the laminated film is transported to the next process in a state where the COP film is laminated on the laminated film, the intense vibration and tension caused by the transport can cause the COP film to fall off the laminated film, leading to deterioration of operability and a decrease in yield.
[0008] In view of the above problems, the object of the present invention is to provide a COP process film that has an appropriate degree of adhesion to a COP film to the extent that it is prevented from falling off from the COP film even when the process film is transported in a state in which the COP film is laminated thereon, while at the same time has the contradictory effects of being able to be smoothly peeled off from the COP film after drying, and further has excellent surface smoothness. [Means for solving the problem]
[0009] As a result of intensive research into solving the above-mentioned problems, the inventors discovered that the above-mentioned problems can be solved by using a process film in which a resin layer having a specific composition is formed on a polyester film, and thus arrived at the present invention.
[0010] That is, the gist of the present invention is the following (1) to (7). (1) A film having a resin layer on at least one surface of a polyester film, the resin layer containing an acid-modified ethylene-α-olefin copolymer and a crosslinking agent, the α-olefin component in the acid-modified ethylene-α-olefin copolymer having 5 or more carbon atoms, and the arithmetic average roughness (Sa) of the resin layer surface being 15 nm or less; thermoplastic Film for cycloolefin polymer film manufacturing process. (2) thermoplastic The film according to (1), having a peel strength from a cycloolefin polymer film of 0.05 N / cm or more and 0.50 N / cm or less. thermoplastic Film for cycloolefin polymer manufacturing process. (3) The acid-modified ethylene-α-olefin copolymer according to (1) or (2), wherein the content of the acid-modified component in the acid-modified ethylene-α-olefin copolymer is 1 to 10% by mass. thermoplastic Film for cycloolefin polymer manufacturing process. (4) The composition according to any one of (1) to (3), characterized in that the resin layer contains a wetting agent. thermoplastic Film for cycloolefin polymer manufacturing process. (5) A method for producing a film for a thermoplastic cycloolefin polymer production process according to any one of (1) to (4) above, wherein the α-olefin component has 5 or more carbon atoms. The method includes a step of applying a liquid material for forming a resin layer, which contains an acid-modified ethylene-α-olefin copolymer and a crosslinking agent, onto at least one surface of a polyester film, and a step of drying the liquid material to form a resin layer. thermoplastic A method for producing a film for use in the cycloolefin polymer film production process. (6) The α-olefin component has 5 or more carbon atoms. The method includes a step of applying a resin layer-forming liquid material containing an acid-modified ethylene-α-olefin copolymer and a crosslinking agent onto at least one surface of an unstretched or uniaxially stretched polyester film, followed by drying, and a step of orienting and stretching and heat-treating the polyester film together with the resin layer-forming liquid material. (5) The thermoplastic resin A method for producing a film for use in the cycloolefin polymer film production process. (7) On the resin layer surface of the film according to any one of (1) to (4) above thermoplastic A laminate having cycloolefin polymer films laminated thereon. Effect of the Invention
[0011] The process film of the present invention has a suitable adhesion so that the COP film does not fall off even when shaking occurs due to vibration during transportation, and exhibits excellent releasability when peeled off after the process is completed. The COP film obtained by peeling off the process film of the present invention has excellent surface smoothness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below. The process film of the present invention has a resin layer on at least one surface of a polyester film, and the resin layer must contain an acid-modified ethylene-α-olefin copolymer and a crosslinking agent.
[0013] The acid-modified ethylene-α-olefin copolymer is an ethylene-α-olefin copolymer modified with an acid. The ethylene-α-olefin copolymer contains an ethylene component and one or more α-olefin components. Surprisingly, by containing an acid-modified ethylene-α-olefin copolymer having an α-olefin component with 5 or more carbon atoms and a crosslinking agent in the resin layer, a process film that achieves both the opposing effects of adhesion to a COP film and releasability can be obtained. Furthermore, from the viewpoint of improving releasability from a COP film, the carbon number of the α-olefin component is preferably 6 or more, and most preferably 8 or more. Although the cause has not yet been clarified, the applicant's post-hoc speculation is that the adhesion to a COP film is improved by the reaction of ethylene with the crosslinking agent, and the inclusion of an α-olefin component with 5 or more carbon atoms increases the flexibility of the ethylene-α-olefin copolymer, improving the releasability from a COP film. Examples of the α-olefin component having 5 or more carbon atoms include 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, etc. Among these, 1-hexene, 1-heptene, and 1-octene are preferred from the viewpoint of improving releasability.
[0014] The mass ratio of the ethylene component to the α-olefin component in the ethylene-α-olefin copolymer (ethylene / α-olefin) is preferably 60 / 40 to 99 / 1. By setting the mass ratio of the ethylene component to the α-olefin component in the ethylene-α-olefin copolymer within the above range, the obtained resin layer can have both good adhesion to the COP film and good releasability. In addition, by setting the mass ratio within the above range, the content of the acid-modified component can be adjusted to the content described below, and the obtained acid-modified ethylene-α-olefin copolymer can be easily dispersed in water. From the viewpoint of improving releasability from the COP film, the content of the α-olefin component in the ethylene-α-olefin copolymer is preferably 1 to 40% by mass.
[0015] The ethylene-α-olefin copolymer before acid modification preferably has a weight average molecular weight of 15,000 to 200,000, more preferably 15,000 to 150,000, and even more preferably 20,000 to 100,000. By using an ethylene-α-olefin copolymer having a weight average molecular weight within the above range, the content of the acid-modified component can be set within the range described below, and the molecular weight after acid modification can be adjusted to the range described below, making it possible to obtain a desirable process film.
[0016] The ethylene-α-olefin copolymer is preferably produced using a metallocene catalyst, which has a narrow molecular weight distribution, a small amount of low molecular weight components, and a uniform copolymerization.
[0017] In the present invention, the ethylene-α-olefin copolymer is acid-modified, and reacts with the crosslinking agent to improve the adhesion between the resin layer and the polyester film, improve the heat resistance, and suppress the transfer of the resin component during peeling. The acid modification of the ethylene-α-olefin copolymer can be carried out, for example, by introducing an unsaturated carboxylic acid component into the ethylene-α-olefin copolymer.
[0018] Specific examples of the unsaturated carboxylic acid component introduced into the ethylene-α-olefin copolymer include acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, aconitic acid, aconitic anhydride, fumaric acid, crotonic acid, citraconic acid, mesaconic acid, allylsuccinic acid, etc., as well as compounds having at least one carboxyl group or acid anhydride group in the molecule (monomer unit), such as half esters and half amides of unsaturated dicarboxylic acids. Among them, from the viewpoint of ease of introduction into the ethylene-α-olefin copolymer, maleic anhydride, acrylic acid, and methacrylic acid are preferred, and maleic anhydride is more preferred. The unsaturated carboxylic acid component may be copolymerized in the ethylene-α-olefin copolymer, and the form is not limited, and examples thereof include random copolymerization, block copolymerization, and graft copolymerization.
[0019] In the present invention, the content of the acid-modified component constituting the acid-modified ethylene-α-olefin copolymer is preferably 1 to 10 mass%, more preferably 1 to 5 mass%, even more preferably 1.5 to 4.5 mass%, and most preferably 2 to 4.5 mass%. By making the content of the acid-modified component 1 mass% or more, it becomes easy to react with the crosslinking agent, and not only the adhesion to the polyester film is improved, but also the releasability and heat resistance from the COP film are improved. By making the content of the acid-modified component 10 mass% or less, sufficient releasability from the COP film is obtained.
[0020] The method of introducing the unsaturated carboxylic acid unit into the ethylene-α-olefin copolymer is not particularly limited. For example, in the presence of a radical generator, the ethylene-α-olefin copolymer and the unsaturated carboxylic acid are reacted by heating and melting the ethylene-α-olefin copolymer to a temperature above the melting point of the ethylene-α-olefin copolymer, or the ethylene-α-olefin copolymer and the unsaturated carboxylic acid are dissolved in an organic solvent, and then heated and stirred in the presence of a radical generator to react, thereby graft-copolymerizing the unsaturated carboxylic acid onto the ethylene-α-olefin copolymer. The former method is preferred because of its simple operation. Examples of the radical generator used in the graft copolymerization include organic peroxides such as di-tert-butyl peroxide, dicumyl peroxide, tert-butyl hydroperoxide, tert-butyl cumyl peroxide, benzoyl peroxide, dilauryl peroxide, cumene hydroperoxide, tert-butyl peroxybenzoate, methyl ethyl ketone peroxide, di-tert-butyl diperphthalate, etc., and azonitriles such as azobisisobutyronitrile, etc. These may be appropriately selected and used depending on the reaction temperature.
[0021] In the present invention, the acid-modified ethylene-α-olefin copolymer may be copolymerized with a small amount of other monomers within the range not impairing the effects of the present invention, from the viewpoint of improving adhesion to polyester film. Examples of other monomers include (meth)acrylic acid esters, olefins other than α-olefins, dienes, (meth)acrylonitrile, vinyl halides, vinylidene halides, carbon monoxide, and sulfur disulfide. On the other hand, from the viewpoint of mold releasability, it is preferable that the other monomers are not contained. The content of other monomer components is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably zero, based on the mass of the acid-modified ethylene-α-olefin copolymer.
[0022] In the present invention, the weight average molecular weight of the acid-modified ethylene-α-olefin copolymer is preferably 20,000 to 300,000, more preferably 20,000 to 200,000, and most preferably 30,000 to 100,000, from the viewpoints of ease of liquefaction into a liquid material for forming a resin layer, releasability from a COP film, and contamination resistance. When the acid-modified ethylene-α-olefin copolymer has a weight average molecular weight within the above range, it is easy to produce a solution or aqueous dispersion that is uniform and well dispersed.
[0023] In the present invention, a commercially available ethylene-α-olefin copolymer can be used as the ethylene-α-olefin copolymer to be acid-modified. Examples of commercially available ethylene-α-olefin copolymers include the Esprene series manufactured by Sumitomo Chemical Co., Ltd., the Tafmer series manufactured by Mitsui Chemicals, Inc., and the Engage series and Affinity series manufactured by Dow Chemical Co., Ltd. Using such a commercially available ethylene-α-olefin copolymer, acid modification can be performed by the above-mentioned method to obtain an acid-modified ethylene-α-olefin copolymer.
[0024] In the present invention, a compound having multiple functional groups in the molecule that react with the acid-modified ethylene-α-olefin copolymer is used as the crosslinking agent, and from the viewpoint of reactivity, an oxazoline compound or a carbodiimide compound is preferred, and an oxazoline compound is most preferred. When an oxazoline compound or a carbodiimide compound is used as a crosslinking agent, the crosslinking reaction can be sufficiently carried out, and the resulting resin layer has heat resistance and does not decrease in releasability after heat treatment.
[0025] The oxazoline compound is not particularly limited as long as it has two or more oxazoline groups in the molecule. For example, compounds having an oxazoline group such as 2,2'-bis(2-oxazoline), 2,2'-ethylene-bis(4,4'-dimethyl-2-oxazoline), 2,2'-p-phenylene-bis(2-oxazoline), and bis(2-oxazolinylcyclohexane) sulfide, and oxazoline group-containing polymers can be mentioned. One or more of these can be used. Among these, oxazoline group-containing polymers are preferred because of their ease of handling. The oxazoline group-containing polymer is obtained by polymerizing an addition-polymerizable oxazoline such as 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, or 2-isopropenyl-2-oxazoline. If necessary, other monomers may be copolymerized. The polymerization method of the oxazoline group-containing polymer is not particularly limited, and various known polymerization methods can be adopted. Commercially available oxazoline group-containing polymers include the Epocross series manufactured by Nippon Shokubai Co., Ltd., specifically the water-soluble types "WS-300," "WS-500," and "WS-700," and the solid type "RPS-1005."
[0026] In the present invention, the content of the crosslinking agent is preferably 5 to 80 parts by mass relative to 100 parts by mass of the acid-modified ethylene-α-olefin copolymer. More preferably, it is 5 to 50 parts by mass, and even more preferably, it is 5 to 25 parts by mass. If the content of the crosslinking agent is less than 5 parts by mass relative to 100 parts by mass of the acid-modified ethylene-α-olefin copolymer, the effect of addition is poor, and the releasability from the COP film may be poor, and the blocking resistance may be deteriorated. On the other hand, if the content of the crosslinking agent is more than 80 parts by mass relative to 100 parts by mass of the acid-modified ethylene-α-olefin copolymer, the liquid stability may be deteriorated, the releasability may be reduced over time, and the arithmetic average roughness (Sa) of the resin layer surface may be increased. In addition, two or more kinds of crosslinking agents can be used simultaneously. When used simultaneously, the total amount of the crosslinking agents should be within the range of the content of the crosslinking agents described above. A catalyst may be contained from the viewpoint of promoting the crosslinking reaction and increasing the crosslinking rate.
[0027] In the present invention, a wetting agent may be contained from the viewpoint of changing the rheological properties of the liquid material for forming the resin layer and improving the coating property as a leveling agent. It is desirable that the wetting agent has a low surface tension and a high coating effect. From the viewpoint of improving the coating property and the surface smoothness of the resin layer, the content of the wetting agent in the total blend amount of the liquid material for forming the resin layer is preferably 1.5% by mass or less, more preferably 1% by mass or less, and most preferably 0.5% by mass or less. Usually, the wetting agent exerts the above effect by containing about 0.02% by mass of the total blend amount. Note that two or more types of wetting agents can be used simultaneously, and when two or more types of wetting agents are used simultaneously, the total content of the wetting agents may be within the above range.
[0028] As the wetting agent, commercially available products can be used, and examples thereof include "Surfynol PSA-336", "Surfynol 420", "Olfine EXP.4200", and "Olfine E1010" manufactured by Nissin Chemical Industry Co., Ltd., and "Polyflow KL-900" manufactured by Kyoeisha Chemical Co., Ltd.
[0029] In the present invention, from the viewpoint of improving the liquid stability and wettability of the resin layer forming coating liquid, a hydrophilic polymer may be contained as another resin. Examples of the hydrophilic polymer include sodium polyacrylate, carboxyvinyl polymer, polyacrylic acid amide, acrylamide / acrylate copolymer, polyvinyl alcohol, polyvinylpyrrolidone, and copolymers thereof. Among them, polyvinyl alcohol or polyvinylpyrrolidone and / or copolymers thereof, which are vinyl-based hydrophilic polymers, are preferred.
[0030] Commercially available polyvinyl alcohol can be used, such as "JP-15", "JT-05", "JF-05", "JL-05E", "JM-17", "VC-10", "JF-10", and "JC-10" from "J-Poval" manufactured by Japan Vinyl Acetate & Poval Corporation, and "PVA-CST", "PVA-624", "PVA-203", "PVA-220", and "PVA-405" from "Kuraray Poval" manufactured by Kuraray Co., Ltd.
[0031] Commercially available polyvinylpyrrolidone can be used, such as "K-30L", "K-60L", "K-90L", and "V-7154" of "Pittscol" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., and "K-30", "K-85", and "K-90" of "Polyvinylpyrrolidone" manufactured by Nippon Shokubai Co., Ltd.
[0032] The content of the hydrophilic polymer is preferably 600 parts by mass or less, and more preferably 10 to 600 parts by mass, relative to 100 parts by mass of the acid-modified ethylene-α-olefin copolymer. Two or more kinds of hydrophilic polymers can be used simultaneously, and when two or more kinds of hydrophilic polymers are used simultaneously, it is sufficient that the total content of the hydrophilic polymers satisfies the above range.
[0033] In the present invention, a defoaming agent may be added from the viewpoint of improving defoaming properties during coating. Commercially available defoaming agents can be used, for example, "Surfynol" manufactured by Nissin Chemical Industry Co., Ltd. DF110D", "Surfynol AD001", "Surfynol MD-20", etc. San Nopco's "SN Deformer 154" etc.
[0034] In the present invention, from the viewpoint of improving adhesion to the COP film, an acid-modified polyolefin resin different from the acid-modified ethylene-α-olefin copolymer may be further contained. The acid-modified polyolefin resin is a resin containing an olefin component as a main component and modified with an acid component. Examples of the olefin component include alkenes having 2 to 6 carbon atoms such as ethylene, propylene, isobutylene, 2-butene, 1-butene, 1-pentene, and 1-hexene, and mixtures thereof may also be used.
[0035] The content of the acid-modified polyolefin resin is preferably 600 parts by mass or less, and more preferably 1 to 600 parts by mass, based on 100 parts by mass of the acid-modified ethylene-α-olefin copolymer.
[0036] The acid-modified component constituting the acid-modified polyolefin resin includes unsaturated carboxylic acid components, specifically acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, crotonic acid, etc., as well as half esters and half amides of unsaturated dicarboxylic acids. Among them, in order to stably disperse the resin in the aqueous dispersion of the resin described later, acrylic acid, methacrylic acid, maleic acid, and maleic anhydride are preferred, and acrylic acid, methacrylic acid, and maleic anhydride are particularly preferred. Two or more of these acid-modified components may be contained in the acid-modified polyolefin resin. The proportion of the acid-modified component in the acid-modified polyolefin resin is not particularly limited, but is preferably 1 to 10% by mass.
[0037] The acid-modified polyolefin resin may contain an ethylenically unsaturated component containing an oxygen atom in the side chain. Examples of ethylenically unsaturated components containing oxygen atoms in the side chain include esters of (meth)acrylic acid and alcohols having 1 to 30 carbon atoms, and among these, from the viewpoint of availability, esters of (meth)acrylic acid and alcohols having 1 to 20 carbon atoms are preferred. Specific examples of such compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, and stearyl (meth)acrylate. A mixture of these may be used. Among these, from the viewpoint of adhesion to polyester film, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hexyl acrylate, and octyl acrylate are more preferred, ethyl acrylate and butyl acrylate are even more preferred, and ethyl acrylate is particularly preferred. "(meth)acrylic acid" means "acrylic acid or methacrylic acid". The proportion of ethylenically unsaturated components containing oxygen atoms in the side chains in the acid-modified polyolefin resin is not particularly limited, but is preferably 1 to 40% by mass.
[0038] The resin layer of the process film of the present invention may contain diene rubber, tackifier, etc. for the purpose of improving adhesion to the COP film, and from the viewpoint of handleability, it is preferable to use a water-based emulsion of the diene rubber, tackifier, etc.
[0039] The diene rubber is not particularly limited, and examples thereof include isoprene rubbers including natural rubber (NR) and polyisoprene rubber (IR), butadiene rubber (BR), styrene-butadiene copolymer rubber (SBR), styrene-isoprene-butadiene copolymer rubber (SIBR), chloroprene rubber (CR); acid-modified products and hydrogenated products of these rubbers.
[0040] The tackifier is not particularly limited, and examples thereof include petroleum resin-based tackifiers: rosin-based tackifiers such as rosin and rosin derivatives; terpene-based tackifiers such as terpene resins, hydrogenated terpene resins, terpene phenol resins, and aromatic modified terpene resins.
[0041] From the viewpoint of achieving both adhesion and releasability between the film of the present invention and the COP film, the amount is preferably 300 parts by mass or less, and more preferably 0.1 to 300 parts by mass, per 100 parts by mass of the acid-modified ethylene-α-olefin copolymer.
[0042] The process film of the present invention may contain various agents such as defoamers, anti-foaming agents, antistatic agents, pigment dispersants, and ultraviolet absorbing agents in the resin layer as necessary, as well as pigments or dyes such as titanium oxide, zinc oxide, and carbon black. In addition, organic or inorganic compounds other than those mentioned above may be added to the liquid material to be used to form the resin layer, as long as the stability of the liquid material is not impaired.
[0043] In the present invention, the thickness of the resin layer is preferably 0.01 to 5.0 μm, more preferably 0.03 to 3.0 μm, and further preferably 0.05 to 1.0 μm. If the thickness of the resin layer is less than 0.01 μm, sufficient releasability may not be obtained, while if the thickness exceeds 5.0 μm, the cost increases, which is not preferable.
[0044] In the present invention, a method for forming a resin layer includes applying a liquid for forming a resin layer containing an acid-modified ethylene-α-olefin copolymer and a crosslinking agent to at least one surface of a polyester film and drying the liquid to form a resin layer on at least one surface of the polyester film.
[0045] The liquid material for forming a resin layer containing an acid-modified ethylene-α-olefin copolymer and a crosslinking agent may be used by dissolving the resin and the crosslinking agent in an organic solvent or dispersing them in an aqueous medium or solvent, but it is preferable to use it as an aqueous medium from the viewpoint of handling the liquid material and the safety and hygiene of the working environment. The aqueous dispersion is a dispersion of the above-mentioned acid-modified ethylene-α-olefin copolymer in an aqueous medium, and the acid-modified ethylene-α-olefin copolymer is dispersed or dissolved in the aqueous medium by 1%. In the present invention, the aqueous medium is a liquid mainly composed of water, and may contain a basic compound or an organic solvent described below in order to promote the aqueousization of the acid-modified ethylene-α-olefin copolymer.
[0046] In the present invention, the liquid medium constituting the resin layer-forming liquid material is preferably an aqueous medium. The aqueous medium means a solvent containing water and an amphipathic organic solvent and having a water content of 2% by mass or more, or may be water alone. An amphipathic organic solvent refers to an organic solvent in which the solubility of water in the organic solvent at 20°C is 5 mass% or more (the solubility of water in organic solvents at 20°C is described in literature such as "Solvent Handbook" (Kodansha Scientific, 10th edition, 1990)).
[0047] The liquid material for forming the resin layer may contain additives such as antioxidants, ultraviolet absorbers, lubricants, colorants, and antifoaming agents, as long as the additives do not impair the properties of the liquid material.
[0048] The liquid for forming the resin layer is preferably a polyolefin resin aqueous dispersion. In the polyolefin resin aqueous dispersion, the acid-modified component in the acid-modified ethylene-α-olefin copolymer is preferably neutralized with a basic compound. The electrical repulsive force between the anions generated by the neutralization of the acid-modified component prevents aggregation between the fine particles of the acid-modified ethylene-α-olefin copolymer, imparting stability to the aqueous dispersion. The basic compound used for the aqueous dispersion may be any compound capable of neutralizing the acid-modified component. The basic compound is preferably ammonia or an organic amine compound that volatilizes during coating film formation from the viewpoint of the water resistance of the coating film, and among these, an organic amine compound having a boiling point of 30 to 250°C, more preferably 50 to 200°C, is preferred. If the boiling point is less than 30°C, a large proportion of the resin volatilizes during the aqueous conversion of the resin described below, and the aqueous conversion may not proceed completely. If the boiling point exceeds 250°C, it becomes difficult to disperse the organic amine compound from the resin coating film by drying, and the water resistance of the coating film may decrease.
[0049] In order to promote the aqueous conversion of the acid-modified ethylene-α-olefin copolymer and reduce the dispersed particle size, it is preferable to add a hydrophilic organic solvent during the aqueous conversion. The content of the hydrophilic organic solvent is preferably 50% by mass or less, more preferably 1 to 45% by mass, even more preferably 2 to 40% by mass, and particularly preferably 3 to 35% by mass, based on the total aqueous medium. If the content of the hydrophilic organic solvent exceeds 50% by mass, the medium cannot be regarded as an aqueous medium, which not only deviates from one of the objects of the present invention (improvement of the working environment), but also may reduce the stability of the aqueous dispersion depending on the hydrophilic organic solvent used.
[0050] A method for producing an aqueous polyolefin resin dispersion, which is one of the liquid materials for forming a resin layer, will be described. The method for producing the polyolefin resin aqueous dispersion is not limited as long as the acid-modified ethylene-α-olefin copolymer is uniformly mixed and dispersed in the aqueous medium. For example, the acid-modified ethylene-α-olefin copolymer, the hydrophilic organic solvent, the basic compound, water and other raw materials are charged into a sealable container, and the mixture is stirred while maintaining the temperature in the container at about 40 to 150° C. to obtain an aqueous dispersion.
[0051] The content of the acid-modified ethylene-α-olefin copolymer in the polyolefin resin aqueous dispersion is appropriately adjusted depending on the film-forming conditions, the desired thickness and performance of the resin layer, etc., and is not particularly limited. However, in order to maintain an appropriate viscosity of the aqueous dispersion and obtain a good coating film and resin layer, the solid content is preferably 1 to 50 mass%, and more preferably 5 to 40 mass%.
[0052] In addition, after forming a resin layer on a polyester film, aging treatment may be performed in an environment controlled at a constant temperature in order to promote the reaction between the acid-modified ethylene-α-olefin copolymer and the crosslinking agent. The aging temperature is preferably relatively low from the viewpoint of reducing damage to the substrate, but is preferably performed at a high temperature from the viewpoint of allowing the reaction to proceed sufficiently and quickly. The aging treatment is preferably performed at 20 to 100°C, more preferably at 30 to 70°C, and even more preferably at 40 to 60°C.
[0053] The polyester film constituting the process film of the present invention preferably has mechanical strength and dimensional stability. The polyester resin constituting the polyester film can be a known polyester resin, such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), poly(1,4-cyclohexylene dimethylene terephthalate), polylactic acid (PLA), etc. These may be used alone or in combination of two or more.
[0054] In the present invention, the polyester film may contain known additives and stabilizers, such as antistatic agents, plasticizers, lubricants, antioxidants, etc. These additives may be used alone or in combination of two or more kinds.
[0055] When the polyester film is laminated with other materials, the surface may be subjected to a pretreatment such as corona treatment, plasma treatment, ozone treatment, chemical treatment, solvent treatment, etc., in order to improve adhesion.
[0056] In addition, silica, alumina, etc. may be vapor-deposited, and other layers such as a barrier layer, an easy-adhesion layer, an antistatic layer, and an ultraviolet absorbing layer may be laminated.
[0057] In the present invention, the polyester film may be a single-layer film consisting of one type of layer, or may have a multilayer structure consisting of two or more types of layers laminated together, with a multilayer structure being preferred from the viewpoint that the surface roughness of each side of the polyester film can be controlled independently.
[0058] When a multilayer film is used as the polyester film, the layer on which the resin layer is provided preferably does not contain the above-mentioned surface-roughening substance. By not containing a surface-roughening substance in the layer on which the resin layer is provided, the surface-roughening substance does not bleed out to the interface with the resin layer or to the surface of the resin layer, and this makes it possible to prevent a decrease in adhesion between the resin layer and the polyester film and contamination of the adherend during peeling.
[0059] A film having a multilayer structure can be produced by a method of separately melting the polyesters constituting each layer, extruding them using a multilayer die, laminating and fusing them before solidification, and then biaxially stretching and heat fixing them, or by a method of separately melting and extruding two or more polyesters to form films, and laminating and fusing them in an unstretched state or after stretching them, etc. From the viewpoint of process simplicity, it is preferable to use a multilayer die and laminate and fusing them before solidification.
[0060] The thickness of the polyester film constituting the process film of the present invention is not particularly limited, but is usually preferably from 12 to 200 μm, and more preferably from 12 to 50 μm.
[0061] Next, an example of a method for producing the process film of the present invention will be described. A polyester resin that has been thoroughly dried is fed into an extruder, melted at a temperature at which it is sufficiently plasticized and exhibits fluidity, and then passed through a selected filter as necessary, and then extruded into a sheet through a T-die. This sheet is brought into close contact with a cooling drum whose temperature is adjusted to a temperature below the glass transition temperature (Tg) of the polyester resin, to obtain an unstretched film. A liquid material for forming a resin layer containing an acid-modified ethylene-α-olefin copolymer and a crosslinking agent is applied onto at least one surface of the obtained unstretched film, and then dried. It is preferable to include a step of stretching and heat-treating the polyester film having the resin layer formed thereon. The stretching method is not particularly limited, but the process film of the present invention can be produced by using a sequential biaxial stretching method or a simultaneous biaxial stretching method.
[0062] The resin layer is preferably provided on the side of the polyester film having a smooth surface roughness, and may be provided on both sides.
[0063] The heat shrinkage of the process film of the present invention in heat treatment at 160° C. for 15 minutes is preferably 2.0% or less in the MD and TD directions, and the lower the better. If the heat shrinkage is low, the COP film is less likely to have defects even after coating and drying.
[0064] The surface roughness Sa of the resin layer constituting the process film of the present invention must be 15 nm or less, preferably 10 nm or less, and most preferably 5 nm or less, from the viewpoint of improving the surface smoothness of the COP film obtained by peeling. If the surface roughness Sa of the resin layer is 15 nm or less, defects are unlikely to occur even if the surface condition of the process film is transferred to the COP film in the COP film manufacturing process.
[0065] By applying a coating liquid for forming a resin layer containing the above-mentioned acid-modified ethylene-α-olefin copolymer to a polyester film surface that does not contain a roughening substance and forming a resin layer, the surface roughness Sa of the resin layer surface can be reduced to 15 nm or less.
[0066] The maximum surface height Sz of the resin layer surface constituting the process film of the present invention is preferably 1 μm or less, more preferably 0.5 μm or less, and most preferably 0.2 μm or less, from the viewpoint of suppressing transfer of the resin layer surface to the COP film.
[0067] In the present invention, the surface roughness Sa of the polyester film surface is preferably 2 nm or more. When the surface roughness Sa is 2 nm or more, the slipperiness is good, and therefore problems such as wrinkles during film winding, scratches during roll storage, and roughness of the film surface during unwinding due to blocking can be prevented.
[0068] In the sequential biaxial stretching method, an unstretched film is heated by a roll, infrared rays, or the like, and stretched in the longitudinal direction to obtain a longitudinally stretched film. The stretching is preferably performed by utilizing the peripheral speed difference between two or more rolls, and is preferably performed at 2.5 to 4.0 times in the range of Tg to 40°C higher than Tg of the polyester. The longitudinally stretched film is then continuously subjected to transverse stretching, heat setting, and heat relaxation in the width direction to obtain a biaxially oriented film. The transverse stretching is started at a temperature 40°C higher than Tg of the polyester, and the maximum temperature is preferably a temperature (100 to 40)°C lower than the melting point (Tm) of the polyester. The ratio of the transverse stretching is adjusted depending on the required physical properties of the final film, but is preferably 3.5 times or more, further preferably 3.8 times or more, and more preferably 4.0 times or more. After stretching in the longitudinal direction and the width direction, the film can be further stretched again in the longitudinal direction and / or the width direction to increase the elastic modulus and dimensional stability of the film. When manufacturing a process film by the above-mentioned sequential biaxial stretching method, there are a method in which a liquid is applied to an unstretched film and then stretched longitudinally and transversely, and a method in which a liquid is applied to a longitudinally stretched film and then stretched transversely. The latter method is preferred for reasons of simplicity and operation.
[0069] Following the stretching, it is preferable to carry out a heat setting treatment for several seconds at a temperature (50 to 10)°C lower than the Tm of the polyester, and simultaneously relax the film by 2 to 10% in the width direction of the film. After the heat setting treatment, the film is cooled to a temperature below the Tg of the film to obtain a biaxially stretched film provided with a resin layer.
[0070] Since the process film of the present invention has an appropriate adhesion to a COP film material, a laminate can be formed by laminating a COP film material on a resin layer.
[0071] The laminate of the present invention has a COP film provided on the resin layer surface of a film for processing.
[0072] The process film of the present invention has excellent peelability from the COP film after the process is completed. The peel strength between the process film and the COP film is preferably 0.05 N / cm or more and 0.50 N / cm or less. If the peel strength is within the range of 0.05 N / cm or more and 0.50 N / cm or less, the COP film will not fall off during transport of the laminate, and the process film can be smoothly peeled off from the COP film when peeling. More preferably, the peel strength is 0.05 N / cm or more and 0.25 N / cm or less. Most preferably, the peel strength is 0.05 N / cm or more and 0.20 N / cm or less.
[0073] When the process film of the present invention is wound into a roll, it is desirable that the components of the resin layer of the process film do not migrate to the back surface (the surface of the polyester film on which no resin layer is formed).
[0074] Examples of cycloolefin polymers include thermoplastic olefin resins having a cyclic olefin skeleton in the main chain, as described in JP-A-10-120768, JP-A-11-43566, JP-A-2004-51949, JP-A-2004-156048, etc. Commercially available cycloolefin polymers include "ARTON" manufactured by JSR Corporation, "ZEONOR" and "ZEONEX" manufactured by Zeon Corporation, "TOPAS" manufactured by Polyplastics Co., Ltd., and "APEL" manufactured by Mitsui Chemicals, Inc. EXAMPLES
[0075] The present invention will be specifically explained below with reference to examples, but the present invention is not limited to these. Various characteristics were measured or evaluated by the following methods.
[0076] 1.Measurement method In the present invention, various evaluations were carried out by the following methods. (1) Content of unsaturated carboxylic acid component in acid-modified ethylene-α-olefin copolymer Fourier transform infrared spectrophotometer (PerkinElmer, System-2000, resolution 4 cm -1 ) was used to perform infrared absorption spectrum analysis to determine the content of unsaturated carboxylic acid components.
[0077] (2) Structure of the acid-modified ethylene-α-olefin copolymer other than the unsaturated carboxylic acid component In orthodichlorobenzene (d4) at 120°C, 1 H-NMR, 13 The results were obtained by C-NMR analysis (Varian, 300 MHz). 13 The C-NMR analysis was performed using the gated decoupling method, taking into account quantitative analysis.
[0078] (3) Weight average molecular weight The weight average molecular weight was measured by GPC analysis (Shimadzu Corporation, LC-10AD type, using two SHODEX KF-804L columns and one KF805L column connected together) using tetrahydrofuran as the eluent at a flow rate of 1 ml / min and 40°C. Approximately 10 mg of the copolymer was dissolved in 5.5 mL of tetrahydrofuran and filtered through a PTFE membrane filter to prepare a measurement sample. The weight average molecular weight was determined from a calibration curve prepared using a polystyrene standard sample.
[0079] (4) Solid content concentration An appropriate amount of the aqueously dispersed acid-modified ethylene-α-olefin copolymer was weighed out and heated at 150° C. until the mass of the remaining matter (solid content) reached a constant weight, and the solid content concentration was determined.
[0080] (5) Adhesion to COP film A liquid prepared by dissolving COP (JSR Corporation's "ARTON®") in a xylene solvent so that the solid content concentration was 35 parts by mass was applied onto the resin layer surface of the obtained process film in a coating amount of approximately 30 g / m2 after drying. 2 This was then dried at 110° C. for 20 minutes to obtain a laminate in which the COP film was laminated onto the process film. Thereafter, in order to check the adhesion between the COP film and the process film, the adhesion was confirmed by the cross-cut method in accordance with JIS K5600-5-6. In detail, an adhesive tape (CT-18 manufactured by Nichiban Co., Ltd.) was applied to the surface of the COP film on which a grid pattern of 100 sections had been cut, and the tape was vigorously peeled off. Note that "100 / 100" indicates a state in which none of the 100 sections have peeled off and the film is in the most adhesive state, and "0 / 100" indicates a state in which all of the 100 sections have peeled off and the film is not in any adhesive state at all. In order to use the film as a process film, the adhesion with the COP film is required to be "100 / 100 to 90 / 100", preferably "100 / 100 to 95 / 100", more preferably "100 / 100 to 98 / 100", and most preferably "100 / 100".
[0081] (6) Surface smoothness of resin layer of processing film Sa (arithmetic mean height), Sz (maximum height) Using a Hitachi High-Tech Nano 3D optical interference measurement system VS1800, the surface roughness parameters Sa (arithmetic mean height, nm) and Sz (maximum height, μm) were measured at 10 points on the resin layer surface of the film, and the average value was taken as the measurement result.
[0082] (7) Surface smoothness Sa (arithmetic mean height) and Sz (maximum height) of the COP film after peeling A liquid prepared by dissolving COP (JSR Corporation's "ARTON®") in a xylene solvent so that the solid content concentration was 35% by mass was applied onto the resin layer surface of the obtained process film in a coating amount of approximately 30 g / m2 after drying. 2 This was then dried at 110° C. for 20 minutes to obtain a laminate in which the COP film was laminated onto the process film. After that, the COP film and the process film were peeled off, and the surface roughness parameters Sa (arithmetic mean height, nm) and Sz (maximum height, μm) were measured at 10 points on the resin layer side of the COP film using a Hitachi High-Tech Nano 3D optical interference measurement system VS1800, and the average value was recorded as the measurement result. The surface roughness Sa of the resin layer side of the COP film after peeling is required to be 15 nm or less, more preferably 10 nm or less, and most preferably 5 nm or less, and the maximum surface height Sz is preferably 1 μm or less, more preferably 0.5 μm or less, and most preferably 0.2 μm or less.
[0083] (8) Releasability from COP film A liquid prepared by dissolving COP (JSR Corporation's "ARTON®") in a xylene solvent so that the solid content concentration was 35% by mass was applied onto the resin layer surface of the obtained process film in a coating amount of approximately 30 g / m2 after drying. 2 The coating was applied using a Mayer bar so that the thickness of the coating became 10 μm, and the coating was dried at 110° C. for 20 minutes to obtain a laminate in which the COP film was laminated onto the process film. (Equivalent to dry 10 μm) After that, the peel strength between the COP film and the process film was measured. The peel strength between the COP film and the process film was also measured in the same manner for a laminate that had been dried at 110° C. for 20 minutes and then redried at 85° C. for 5 minutes. The peel strength was measured in a thermostatic room at 23° C. using a tensile tester (Intesco Precision Universal Material Tester Model 2020) at a peel angle of 180° and a peel speed of 300 mm / min. For use as a processing film, a practical strength of 0.05 N / cm or more and 0.50 N / cm or less is required.
[0084] (9) Coatability (suppression of streak-like defects in coating) The surface of the resin layer of the release film obtained by the above method was irradiated with white light (100 lumens) from a fluorescent lamp at an angle of 5 to 45 degrees, and the presence or absence of streaky interference was visually confirmed. Coatability was evaluated according to the following criteria based on the occurrence of streaky defects over the entire width at the following 10 points. ○: No streak defects were observed at any point △: Can be confirmed at one to three locations ×: Streak-like defects can be seen in more than three locations The evaluation points were 10 points in total, including a point 1 m from one edge of the release film in the longitudinal direction, a point 1 m from the other edge, and 9 equal points between these two points. Straight lines were drawn in the width direction (TD) of the film at each point with a black oil-based pen, and streak-like defects intersecting the straight lines were observed across the entire width of the film.
[0085] (10) Blocking resistance test Ten sheets of release film cut into 10 cm squares were stacked together, pressurized with a load of 10 kg for 24 hours at 60°C in a thermostatic chamber, and then peeled off with tweezers. The degree of blocking was evaluated on the following three scales. Good: No blocking, no snagging when peeling off. △: When peeling off, there is a slight snag or a slight noise is heard. ×: When peeling off, there was a strong snag and damage was observed on the coating surface.
[0086] 2.Material The resin used to form the resin layer was the resin prepared in the following synthesis example. The composition and weight average molecular weight of the fat are shown in the Production Examples (Table 1) described later.
[0087] Synthesis Example 1 80g of ethylene-octene copolymer (mass ratio: ethylene / octene = 71 / 29, weight average molecular weight = 68,000) was dissolved in 350g of xylene under nitrogen atmosphere in a four-neck flask, and then 30g of maleic anhydride as an unsaturated carboxylic acid and 5g of dicumyl peroxide as a radical generator were added over 2 hours while stirring while maintaining the temperature in the system at 140°C, and then reacted for 6 hours. After the reaction was completed, the reaction product obtained was poured into a large amount of acetone to precipitate a resin. This resin was further washed several times with acetone to remove unreacted maleic anhydride, and then dried under reduced pressure to obtain an acid-modified ethylene-α-olefin copolymer P-1.
[0088] Synthesis Example 2 The same procedure was carried out as in Synthesis Example 1, except that an ethylene-octene copolymer (weight average molecular weight = 22,000) having a mass ratio (ethylene / octene) of 95 / 5 was used, to obtain an acid-modified ethylene-α-olefin copolymer P-2.
[0089] Synthesis Example 3 In Synthesis Example 1, the same procedure was carried out except that an ethylene-heptene copolymer (weight average molecular weight = 69,000) having a mass ratio (ethylene / heptene) of 76 / 24 was used instead of the ethylene-octene copolymer, the amount of maleic anhydride was changed to 20 g, and the amount of dicumyl peroxide was changed to 10 g, to obtain an acid-modified ethylene-α-olefin copolymer P-3.
[0090] Synthesis Example 4 In Synthesis Example 1, the same procedure was carried out except that an ethylene-hexene copolymer (weight average molecular weight = 75,000) having a mass ratio (ethylene / hexene) of 75 / 25 was used instead of the ethylene-octene copolymer, the amount of maleic anhydride was changed to 30 g, and the amount of dicumyl peroxide was changed to 10 g, to obtain an acid-modified ethylene-α-olefin copolymer P-4.
[0091] Synthesis Example 5 The same procedure was carried out in Synthesis Example 4, except that an ethylene-pentene copolymer (weight average molecular weight = 72,000) having a mass ratio (ethylene / pentene) of 73 / 27 was used instead of the ethylene-hexene copolymer, to obtain an acid-modified ethylene-α-olefin copolymer P-5.
[0092] Synthesis Example 6 The same procedure was carried out in Synthesis Example 3, except that an ethylene-butene copolymer (weight average molecular weight = 50,000) having a mass ratio (ethylene / butene) of 70 / 30 was used instead of the ethylene-heptene copolymer, to obtain an acid-modified ethylene-α-olefin copolymer P-6.
[0093] Synthesis Example 7 The same procedure was carried out in Synthesis Example 3, except that an ethylene-propylene copolymer (weight average molecular weight = 58,000) having a mass ratio (ethylene / propylene) of 75 / 25 was used instead of the ethylene-heptene copolymer, to obtain an acid-modified ethylene-α-olefin copolymer P-7.
[0094] Synthesis Example 8 The same procedure was carried out as in Synthesis Example 7, except that an ethylene-propylene copolymer (weight average molecular weight = 56,000) having a mass ratio (ethylene / propylene) of 99 / 1 was used, to obtain an acid-modified ethylene-α-olefin copolymer P-8.
[0095] The acid-modified ethylene-α-olefin copolymers P-1 to P-8 are shown in Table 1.
[0096] [Table 1]
[0097] Manufacturing Example 1 Using a stirrer equipped with a sealable pressure-resistant 1L glass container with a heater, 30 g of acid-modified ethylene-α-olefin copolymer P-1, 100 g of tetrahydrofuran, 18 g of triethylamine and 252 g of distilled water were charged into the glass container, and the stirring blade was set to a rotation speed of 300 rpm to stir. While maintaining this state, the heater was turned on to heat, and the temperature inside the system was kept at 120°C and stirred for 60 minutes. After that, the mixture was cooled to room temperature (about 25°C) while stirring in a water bath, and 64.5 g of distilled water was added. The obtained dispersion was placed in a 1L eggplant flask, and while immersed in a hot water bath heated to 60°C, the pressure was reduced using an evaporator, and 176 g of the aqueous medium was distilled off. After cooling, the liquid components in the flask were pressure-filtered (air pressure 0.2 MPa) with a 300-mesh stainless steel filter (wire diameter 0.035 mm, plain weave) to obtain a milky white, uniform aqueous dispersion of acid-modified ethylene-α-olefin copolymer. The above aqueous dispersion of acid-modified ethylene-α-olefin copolymer (solid concentration: 10.5% by mass) and an aqueous solution of an oxazoline compound (Epocross "WS-300", manufactured by Nippon Shokubai Co., Ltd., solid concentration: 10% by mass) were mixed so that the solid content of the oxazoline compound was 20 parts by mass per 100 parts by mass of the acid-modified ethylene-α-olefin copolymer, and a wetting agent (Polyflow KL-900, manufactured by Kyoeisha Chemical Co., Ltd.) was added at 0.2% by mass of the total blend to obtain a liquid E-1 for forming a resin layer.
[0098] Manufacturing Examples 2-28 In Production Example 1, the type of acid-modified ethylene-α-olefin copolymer, the type and content of crosslinking agent, the type and content of hydrophilic polymer, the type and content of acid-modified polyolefin resin, the type and content of wetting agent, and the type and content of tackifying resin were changed as shown in Tables 1 and 2, but the same operations as in Production Example 1 were performed to obtain liquid materials for forming resin layers E-2 to E-6 and E-8 to E-28. Liquid material E-7 for forming a resin layer was prepared by performing the same procedure as in Production Example 1, except that 20 parts by mass of acid-modified ethylene-α-olefin copolymer P-8 was mixed with 100 parts by mass of acid-modified ethylene-α-olefin copolymer P-1.
[0099] Table 2 shows the resin layer forming liquid materials E-1 to E-28.
[0100] [Table 2]
[0101] 3. Manufacturing of process films Example 1 Polyethylene terephthalate B, which contained 0.07% by mass of silica particles (particle diameter 2.3 μm) in polyethylene terephthalate A (polymerization catalyst: antimony trioxide, intrinsic viscosity: 0.62, glass transition temperature: 78°C, melting point: 255°C), was fed into extruder I (screw diameter: 50 mm), and polyethylene terephthalate A was fed into extruder II (screw diameter: 65 mm), respectively, and melted at 280°C, after which the respective melts were merged and laminated in layers before reaching the outlet of the T-die. The layer thickness ratio (I / II) was adjusted to 4 / 6 and the total thickness was adjusted to 600 μm, and the mixture was extruded from the outlet of the T-die, rapidly cooled and solidified to obtain an unstretched polyester film. This unstretched polyester film was stretched 3.5 times at 85° C. using a roll-type longitudinal stretching machine to obtain a longitudinally stretched film. Next, the resin layer-forming liquid E-1 was applied to the polyester film surface on the extruder II side (polyethylene terephthalate A side) of the longitudinally stretched film at a rate of 5 g / m using a 120-mesh gravure roll. 2 Then, the end % of the longitudinally stretched film was continuously held by the clips of a flat-type stretching machine, and stretched 4.5 times laterally under the condition of 100°C, and then heat-treated at 243°C for 3 seconds with a relaxation rate of 3% in the transverse direction to obtain a process film having a thickness of 38 μm, in which a resin layer having a thickness of 0.1 μm was provided on one side of a base film made of two types of two-layer polyester film.
[0102] Examples 2 to 11, 13 to 24, Comparative Examples 1 to 4 The same operation as in Example 1 was carried out, except that the type of the resin layer-forming liquid material in Example 1 was changed as shown in Table 3, to obtain a process film.
[0103] Example 12 Polyethylene terephthalate C, which contained 0.03 mass% of silica particles (particle diameter 2.3 μm) in polyethylene terephthalate A (polymerization catalyst: antimony trioxide, intrinsic viscosity: 0.62, glass transition temperature: 78 ° C, melting point: 255 ° C), was fed into extruder I (screw diameter: 50 mm), and polyethylene terephthalate A was fed into extruder II (screw diameter: 65 mm), respectively, and melted at 280 ° C., and the respective melts were merged and laminated in layers before reaching the outlet of the T-die. The layer thickness ratio (I / II) was adjusted to 4 / 6 and the total thickness was adjusted to 600 μm, and the mixture was extruded from the outlet of the T-die, rapidly cooled and solidified to obtain an unstretched polyester film. This unstretched polyester film was stretched 3.5 times at 85° C. using a roll-type longitudinal stretching machine to obtain a longitudinally stretched film. Next, the resin layer-forming liquid E-1 was applied to the polyester film surface on the extruder II side (polyethylene terephthalate A side) of the longitudinally stretched film at a rate of 5 g / m using a 120-mesh gravure roll. 2 Then, the end % of the longitudinally stretched film was continuously held by the clips of a flat-type stretching machine, and stretched 4.5 times laterally under the condition of 100°C, and then heat-treated at 243°C for 3 seconds with a relaxation rate of 3% in the transverse direction to obtain a process film having a thickness of 38 μm, in which a resin layer having a thickness of 0.1 μm was provided on one side of a base film made of two types of two-layer polyester film.
[0104] Example 25 Polyethylene terephthalate C, which was obtained by adding 4% by mass of silica particles (particle diameter 2.3 μm) to polyethylene terephthalate A (polymerization catalyst: antimony trioxide, intrinsic viscosity: 0.62, glass transition temperature: 78°C, melting point: 255°C), was fed into extruder I (screw diameter: 50 mm), and polyethylene terephthalate A was fed into extruder II (screw diameter: 65 mm), respectively, and melted at 280°C, after which the respective melts were merged and laminated in layers before reaching the outlet of the T-die. The layer thickness ratio (I / II / I) was adjusted to 1 / 8 / 1 and the total thickness was adjusted to 600 μm, and the resulting mixture was extruded from the outlet of the T-die, rapidly cooled and solidified to obtain an unstretched polyester film. This unstretched polyester film was stretched 3.5 times at 85° C. using a roll-type longitudinal stretching machine to obtain a longitudinally stretched film. Next, the resin layer-forming liquid E-1 was applied to the polyester film surface on the extruder I side (polyethylene terephthalate C side) of the longitudinally stretched film at a rate of 5 g / m using a 120-mesh gravure roll. 2 After coating so as to give the desired result, the end % of the longitudinally stretched film was continuously held by the clips of a flat-type stretching machine and stretched horizontally to 4.5 times its original size at 100°C. The film was then heat-treated at 243°C for 3 seconds with a relaxation rate of 3% in the horizontal direction to obtain a 38μm-thick process film having a 0.1μm-thick resin layer on one side of a base film made of two-kind, three-layer polyester film.
[0105] Example 26 Polyethylene terephthalate C, which was obtained by adding 4% by mass of silica particles (particle diameter 2.3 μm) to polyethylene terephthalate A (polymerization catalyst: antimony trioxide, intrinsic viscosity: 0.62, glass transition temperature: 78°C, melting point: 255°C), was fed into extruder I (screw diameter: 50 mm), and polyethylene terephthalate A was fed into extruder II (screw diameter: 65 mm), respectively, and melted at 280°C, after which the respective melts were merged and laminated in layers before reaching the outlet of the T-die. The layer thickness ratio (I / II / I) was adjusted to 1 / 8 / 1 and the total thickness was adjusted to 600 μm, and the resulting mixture was extruded from the outlet of the T-die, rapidly cooled and solidified to obtain an unstretched polyester film. This unstretched polyester film was stretched 3.5 times at 85°C using a roll-type longitudinal stretching machine, and then the end 100% of the longitudinally stretched film was continuously held by the clips of a flat-type stretching machine and stretched 4.5 times laterally at 100°C.The film was then heat-treated at 243°C for 3 seconds with a relaxation rate of 3% in the transverse direction, and then cooled and wound up to obtain a two-type, three-layer biaxially stretched polyester film (thickness 38 μm) with a thickness of 38 μm. The resin layer-forming liquid E-1 was applied to the obtained biaxially stretched polyester film using a Mayer bar, and then dried at 120°C for 20 seconds to obtain a 38 μm-thick process film with a 0.1 μm-thick resin layer.
[0106] Example 27 A film for processing was obtained in the same manner as in Example 26, except that the type of the resin layer-forming liquid material was changed from E-1 to E-10.
[0107] Comparative Example 5 The corona-treated surface of a biaxially oriented polyester resin film ("Emblett PET-38" manufactured by Unitika Ltd., thickness 38 μm) was coated with the resin layer-forming liquid E-1 using a Mayer bar, and then dried at 120°C for 20 seconds to obtain a 38 μm-thick process film with a 0.1 μm-thick resin layer.
[0108] The obtained film for process use was subjected to various evaluations. The results are shown in Table 3.
[0109] [Table 3]
[0110] The process films obtained in Examples 1 to 27 had good adhesion to the COP film and also had excellent releasability from the COP film after drying. In addition, since the resin layer surface of the process film was smooth, the COP film after peeling also had a smooth surface. In particular, the surfaces of the resin layers of the process films of Examples 1 to 25, in which the resin layers were formed by the in-line coating method, were particularly smooth, so that transfer to the COP film was suppressed and a COP film with excellent surface smoothness was obtained.
[0111] In Comparative Examples 1 to 3, since the resin layer did not contain an acid-modified ethylene-α-olefin containing an olefin component having 5 or more carbon atoms, the adhesion to the COP film and the releasability from the COP film after drying were poor.
[0112] In Comparative Example 4, since the resin layer did not contain a crosslinking agent, the releasability from the COP film was poor.
[0113] In Comparative Example 5, the arithmetic mean roughness (Sa) of the resin layer surface exceeded 15 nm, so that the irregularities were transferred to the COP film, and the surface smoothness of the COP film after peeling was poor.
Claims
1. A film having a resin layer on at least one surface of a polyester film, the resin layer contains an acid-modified ethylene-α-olefin copolymer and a crosslinking agent; the α-olefin component in the acid-modified ethylene-α-olefin copolymer has 5 or more carbon atoms; The arithmetic average roughness (Sa) of the resin layer surface is 15 nm or less; Thermoplastic cycloolefin polymer film manufacturing process film.
2. A film for use in a thermoplastic cycloolefin polymer manufacturing process as described in claim 1, having a peel strength with a thermoplastic cycloolefin polymer film of 0.05 N / cm or more and 0.50 N / cm or less.
3. 3. The film for use in the production process of thermoplastic cycloolefin polymers according to claim 1 or 2, wherein the content of the acid-modified component in the acid-modified ethylene-α-olefin copolymer is 1 to 10% by mass.
4. 3. The film for use in the production process of thermoplastic cycloolefin polymers according to claim 1 or 2, characterized in that the resin layer contains a wetting agent.
5. A method for producing a film for a thermoplastic cycloolefin polymer manufacturing process according to claim 1 or 2, comprising the steps of: A step of applying a resin layer-forming liquid material containing an acid-modified ethylene-α-olefin copolymer having an α-olefin component having 5 or more carbon atoms and a crosslinking agent onto at least one surface of a polyester film; drying to form a resin layer; A method for producing a film for use in a thermoplastic cycloolefin polymer film production process, comprising:
6. A process for forming a resin layer, comprising: applying a liquid material for forming a resin layer, the liquid material containing an acid-modified ethylene-α-olefin copolymer having an α-olefin component with 5 or more carbon atoms and a crosslinking agent, onto at least one surface of an unstretched or uniaxially stretched polyester film, and drying the applied liquid material; A step of orienting and stretching the polyester film and heat treating the polyester film together; The method for producing a film for a thermoplastic cycloolefin polymer film production process according to claim 5 , comprising the steps of:
7. A laminate comprising a thermoplastic cycloolefin polymer film laminated on the resin layer surface of the film according to claim 1 or 2.
Citation Information
Patent Citations
Carrier film for manufacturing optical film
JP2004017435A
Adhesive
JP2010084068A
Laminated film
JP2014208465A
Release sheet
JP2016168691A
Mold release sheet and its manufacturing method
JP2020069664A